2021
DOI: 10.1002/jts5.116
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy and prejudice: The mediating role of empathy, social dominance orientation and right‐wing authoritarianism

Abstract: A current shift in intergroup relations research aims to delve deeper into whether, and how, individual differences predict social attitudes. Recent research goes beyond the measurement of typical personality traits and focuses also on the subclinical area of malicious traits. The present studies aimed at exploring the role of one such trait, psychopathy, as a predictor of negative social attitudes. The role of empathy was examined as a key underlying process explaining the relationship between primary and sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Empathy is important for developing meaningful relationships and participating in community to engage in anti‐racist work (Boele et al., 2019). Lower empathy has been linked to racial colorblindness (Mekawi et al., 2017), as well as negative attitudes toward immigrants, increased racism, and right‐wing authoritarianism (Stathi et al., 2021). On the contrary, the development of perspective‐taking skills and empathetic concern is a key component of anti‐racist identity development in children (Thomann & Suyemoto, 2018) and higher levels of openness to diversity (i.e., participating in diverse cultural activities, appreciating diversity in personal growth, comfort with diverse individuals) among young adults (Chao et al., 2015).…”
Section: The Potmentioning
confidence: 99%
“…Empathy is important for developing meaningful relationships and participating in community to engage in anti‐racist work (Boele et al., 2019). Lower empathy has been linked to racial colorblindness (Mekawi et al., 2017), as well as negative attitudes toward immigrants, increased racism, and right‐wing authoritarianism (Stathi et al., 2021). On the contrary, the development of perspective‐taking skills and empathetic concern is a key component of anti‐racist identity development in children (Thomann & Suyemoto, 2018) and higher levels of openness to diversity (i.e., participating in diverse cultural activities, appreciating diversity in personal growth, comfort with diverse individuals) among young adults (Chao et al., 2015).…”
Section: The Potmentioning
confidence: 99%
“…Further, individuals high in SDO are concerned with maintaining power as well as pursuing their self-interests (Shao et al, 2011). Interestingly, previous research has found social dominance to be associated with numerous negative interpersonal factors, such as a lack of empathy for others (Stathi et al, 2021), prejudice towards immigrants and ethnic minorities (Sidanius et al, 2013), and endorsement of social inequality (Kteily et al, 2011) and sexism (Kteily et al, 2012). Given that individuals high in SDO believe in their dominance and authority, they are also more likely to distance themselves from others whom they perceive to be of lower status (Khan et al, 2016).…”
Section: Social Dominancementioning
confidence: 99%